THE ROLE OF PUBLIC SECTOR PROJECT MANAGEMENT WITHIN THE SOUTH AFRICAN PUBLIC SECTOR ENVIRONMENT - MARTINUS M SELEPE; XOLANI THUSI (Social Sciences and Education Research Review)
The study analyses the role of public sector management within the public sector environment. The study seeks to establish the significance and the role of project management in government. The qualitative research methodology is adopted by the study with reference to the desktop approach which is entirely derived from secondary data. The study explores the significance of the nine knowledge areas of project management in government projects. The paradigm shifts of Public Administration from a traditional approach to the New Public Management and post-New Public management brought increasing demands, which required the intervention of the principles of project management. Project management is a difficult process, especially when it involves the project team and other stakeholders working for a long time. The escalating difficulties need the best management principles and mechanisms to determine the utilization of resources. Therefore, public project management can add value to the public sector environment. Project management plays a notable role in ensuring the development of successful projects and completion of projects within the agreed timelines both in the private and public sectors.